Building professional discourse in emerging markets: Language, context and the challenge of sensemaking - Kuznetsov, Andrei; Kuznetsova, Olga (Journal of International Business Studies, 2014)
Using ethnographic evidence from the former Soviet republics, this paper examines a relatively new and mainly unobserved concept in international business literature: the phenomenon of communication disengagement that manifests itself in many emerging markets. We link it to the deficiencies of the local professional business discourse rooted in language limitations, which reflects a lack of experience with the market economy. This hampers cognitive coherence between foreign and local business entities, adding to the liability of foreignness as certain instances of professional experience fail to find adequate linguistic expression, and complicates cross-cultural adjustments, causing multinational companies (MNCs) financial losses. We contribute to the IB literature by examining cross-border semantic sensemaking through a retrospectively constructed observational study. We argue that a relative inadequacy of the national professional idiom is likely to remain a feature of the business environment in post-communist economies for some time, and therefore should be factored into business strategies of MNCs. Consequently, we recommend including discursive hazards in the risk evaluation of international projects.